Molecular Epidemiology over an 11-Year Period (2000 to 2010) of Extended-Spectrum β-Lactamase-Producing Escherichia coli Causing Bacteremia in a Centralized Canadian Region - Peirano, Gisele (American Society for Microbiology, 2012)
A study was designed to assess the importance of sequence types among extended-spectrum β-lactamase (ESBL)-producing Escherichia coli isolates causing bacteremia over an 11-year period (2000 to 2010) in a centralized Canadian region. A total of 197 patients with incident infections were identified; the majority presented with community-onset urosepsis, with a significant increase in the prevalence of ESBL-producing E. coli during the later part of the study. The majority of E. coli isolates produced either CTX-M-15 or CTX-M-14. We identified 7 different major sequence types among 91% of isolates (i.e., the ST10 clonal complex, ST38, ST131, ST315, ST393, ST405, and ST648) and provided insight into their clinical and molecular characteristics. ST38 was the most antimicrobial-susceptible sequence type and predominated during 2000 to 2004 but disappeared after 2008. ST131 was the most antimicrobial-resistant sequence type, and the influx of a single pulsotype of this sequence type was responsible for the significant increase of ESBL-producing E. coli strains since 2007. During 2010, 49/63 (78%) of the ESBL-producing E. coli isolates belonged to ST131, and this sequence type had established itself as a major drug-resistant pathogen in Calgary, Alberta, Canada, posing an important new public health threat within our region. We urgently need well-designed epidemiological and molecular studies to understand the dynamics of transmission, risk factors, and reservoirs for E. coli ST131. This will provide insight into the emergence and spread of this multiresistant sequence type.